2020
DOI: 10.1002/adma.202002189
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Nitrate Synthesis via Ambient Nitrogen Oxidation with Ru‐Doped TiO2/RuO2 Electrocatalysts

Abstract: A facile pathway of the electrocatalytic nitrogen oxidation reaction (NOR) to nitrate is proposed, and Ru‐doped TiO2/RuO2 (abbreviated as Ru/TiO2) as a proof‐of‐concept catalyst is employed accordingly. Density functional theory (DFT) calculations suggest that Ruδ+ can function as the main active center for the NOR process. Remarkably doping Ru into the TiO2 lattice can induce an upshift of the d‐band center of the Ru site, resulting in enhanced activity for accelerating electrochemical conversion of inert N2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
146
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(153 citation statements)
references
References 33 publications
6
146
0
1
Order By: Relevance
“…A recent study has indicated that an upshift of d‐band center facilitates an enhanced activity for accelerating electrochemical conversion of inert N 2 to active NO*. [ 309 ] Therefore, strain may be exploited to actively modulate the activity of NRR.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has indicated that an upshift of d‐band center facilitates an enhanced activity for accelerating electrochemical conversion of inert N 2 to active NO*. [ 309 ] Therefore, strain may be exploited to actively modulate the activity of NRR.…”
Section: Discussionmentioning
confidence: 99%
“…The second step is a redox reaction, in which NO * is transformed into nitrate over the active sites. 116 In this process, the highly active and selective catalyst materials for NOR are very important.…”
Section: Nitrogen Oxidation Reactionmentioning
confidence: 99%
“…In particular, Ti-based materials have been extensively studied due to their high photocatalytic activity and stability. 116,[128][129][130][131][132] Titanium alkoxides prepared by the high-temperature hydrolysis method have shown high denitrification activity, with a high absorption rate of 98% for NO photocatalytic oxidation. 133 In 2008, TiO 2 nanoparticles coating on woven glass fabric was used as a photocatalyst, which showed a good effect for removing nitrogen oxides and an efficiency of 63.9% upon the steady-state.…”
Section: Denitrification Of Gaseous Nitrogen Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest in using catalysts at low cost, rich abundance, and reversibility in terms of oxygen reactions has been growing. Ru–Sn oxides, as well as transitional metal oxides, nitrides, selenides, hydroxides, carbides, phosphides, and their hybrids and/or alloys, have been currently reported 8–13 . However, most of them still underperform the precious metal benchmarks due to their inherent corrodibility and poor electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%